Studi Perencanaan Ulang Bangunan Pelimpah (Spillway) Di Bendungan Semantok Kabupaten Nganjuk - Dimas Enggar Pambudi; Trilita M. Nur; Wahjudijanto Iwan (Universitas Dr. Soetomo, 2024)
The Semantok Dam in Rejoso, Nganjuk, East Java, is intended to address irrigation and domestic water needs around Sebuntal Village, Marangkayu. The spillway is planned to stand perpendicular to the dam body, using the Ogee type I design with various components such as steering channels, transitions, launchers, trumpet launchers, and USBR Type III pool-type energy dampers. The planned discharge for the 1000-year anniversary period reached 302,161 m3/s. The planned dimensions involve a spillway width of 30 meters and a pond length of 19.2 meters. The results of the safety analysis showed that the moment of rolling and sliding under normal conditions reached a value of 1.69 and 2.50, which exceeded the minimum safety standard of 1.5